Usability And Cognitive Load Evaluation of The Threads Interface Using The System Usability Scale (SUS) And NASA-TLX Methods - Kifatul Hasna Tria Widyarsi; Yayak Kartika Sari; Taufiq Agung Cahyono (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The rapid evolution of social media interfaces has reshaped how users consume digital information, and interface complexity is known to affect both ease of use and the mental effort users must invest. This study examines the level of usability and cognitive load of the Threads interface and the relationship between the two constructs, using a quantitative descriptive-correlational approach. An online questionnaire was distributed to 200 students of Universitas Bhinneka PGRI Tulungagung selected through purposive sampling. Usability was measured with the System Usability Scale (SUS) and cognitive load with the NASA Task Load Index (NASA-TLX); data were processed in IBM SPSS. All instruments were valid and reliable, with Cronbach's Alpha values of 0.728 (SUS) and 0.786 (NASA-TLX). The mean SUS score was 70.0875, placing Threads in the